PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN PELANGGAN KAYUMANIS SANUR PRIVATE VILLA AND SPA - Agus Rianto; Saortua Marbun; I Putu Agus Suarsana Ariesta (Journal Research of Management, 2022)
The purpose of this research is to examine the impact of service quality and promotion on customer satisfaction at Kayumanis Sanur Private Villa and Spa. This study employs quantitative research methods in conjunction with a descriptive approach. The sampling method was carried out with specific objectives and considerations with the criteria of customers who had transacted with Kayumanis Sanur Private Villa. The sample size is 80 people, and the data analysis techniques used are descriptive data analysis, validity and reliability testing, the classical assumption test, multiple linear regression, and t test analysis. The results of the analysis show that the regression results are Y = 5.424 + 0.228X1 + 0.166X2. The results of this study show that service quality (X1) has a positive influence, and the most influential variable on customer satisfaction (Y) is shown in the regression coefficient b1X1, which has a positive value of 0.228. The regression coefficient b2X2 has a positive value of 0.166, indicating that promotion (X2) has a positive effect on customer satisfaction (Y). Suggestions for Kayumanis Sanur Private Villa include the need to maintain the quality of service and promotions provided if they need to be improved again in order to achieve customer satisfaction on a consistent basis.